Differences between the practices of innovation environments from National Innovation Systems with distinct maturity levels: insights from Brazilian and French cases - Mathieu, Patrícia Benassi; Delai, Ivete (Revista de Administração da UFSM, 2019)
The aim of this study is to identify the different practices that exist in innovation environments that belong to National Innovation Systems with distinct maturity levels: France (advanced) and Brazil (in development). A case study was carried out comparing the Technological Park of São José dos Campos and the Pôle de Compétitivité HYDREOS regarding seven dimensions: governance, strategy, external relationships, external environment, legal context, infrastructure and funding mechanisms. As a result, the initial premise that the environment inserted into the mature system presents a more comprehensive set of the studied dimensions can be observed. The main differences identified (or improvement opportunities for the Brazilian environment) refer to the following dimensions: external relations, strategy, funding mechanisms and governance. Most of these differences directly affect the degree of interaction between the members of the innovation environment and between them and outsiders, the diversity of actors and the relationship rules, which are key elements of a national innovation system.